Sistem Informasi Manajemen Proyek Kolaboratif Berbasis Web - M Farhan Alyuda; Yahfizham Yahfizham (Router : Jurnal Teknik Informatika dan Terapan, 2024)
For project management software to be efficient and increase productivity, effectiveness, efficiency, security, and functionality, it must be able to accommodate different user needs. It is important to analyze human-computer interactions when designing software to prevent problems that could harm users. To help IT consultants and client organizations in managing and supervising projects more effectively, this author focuses on developing a “Web-Based Collaborative Project Management Information System for Information Technology Project Management”. IT consultants can share data, manage teams, connect with clients, and manage projects, tasks, and milestones with this solution. Business clients have access to IT specialists, can provide project quotes, and can aggregate project status. The waterfall development technique used includes requirements analysis, design, coding, testing, and maintenance. User research shows this.